Building RESTful Python web services : create web services that are lightweight, maintainable, scalable, and secure using the best tools and techniques designed for Python /: create web services that are lightweight, maintainable, scalable, and secure using the best tools and techniques designed for Python. (2016) - Hillar, Gastón C (Gastón Carlos)
No abstract available